Exploring Integrated Instrument Complement at Practical Approach at MAN 4 Tanah Datar - Mutia, Ulfa; Mawarnis, Elvy Rahmi (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The purpose of this research is to produce Integrated Instrument Components. Exploring integrated instrument complement at practical approach at MAN 4 Tanah Datar which is valid and practical. This study uses the Research and Development research method with the 4-D development model (define, design, develop, and disseminate). But the stages in research with this 4-D model are only carried out from the first to the third stage, namely the define stage to get conditions in the field. design stage to prepare a simple practicum kit on Thermochemistry material, and the develop stage to get the results of the initial practicum IIC that has been designed followed by validity and practicality tests. The research instruments used were validation sheets and response questionnaire sheets. The validation sheet was filled in by 2 lecturers and 1 chemistry educator. The response questionnaire sheet was filled by 17 of in 11th grade students of MAN 4 Tanah Datar. The results showed that: 1) Simple Practical IIC on Thermochemical Material has met the valid criteria with 92% validation results, 2) Simple Practical IIC on Thermochemical Material has met the practical criteria with the results of the student response questionnaire.